2020
DOI: 10.47312/ambr.v5i2.325
|View full text |Cite
|
Sign up to set email alerts
|

Servicescape and Group References in Determining Hedonic Value and Its Implication on Impulsive Buying

Abstract: Consumer decision in purchasing product generally depend on his/her needs. The impulsive buying as the purchasing activity, in contrast, was based on the emotional encouragement. In the other hand, customer got pleasant experiences after purchasing that product spontaneously. That is a hedonic value which is customer circumstances encouraging buying decision. This study objectives were to know whether the servicescape and reference group could be determinant factors of hedonic value and impulsive buying activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Fifth: Nugraha and Abdullah [24] conducted a study titled "The Effect of Physical Environment and Hedonic Shopping Value on Unplanned Purchases at Giant Express Cilegon." It concluded that the research outcomes showed that the servicescape and reference group significantly affect the hedonic value and have implications for partial and simultaneous impulse buying.…”
Section: Resultsmentioning
confidence: 99%
“…Fifth: Nugraha and Abdullah [24] conducted a study titled "The Effect of Physical Environment and Hedonic Shopping Value on Unplanned Purchases at Giant Express Cilegon." It concluded that the research outcomes showed that the servicescape and reference group significantly affect the hedonic value and have implications for partial and simultaneous impulse buying.…”
Section: Resultsmentioning
confidence: 99%